Construction of high-energy-density supercapacitors from pine-cone-derived high-surface-area carbons - Amaresh, S. (2014)
Very high surface area activated carbons (AC) are synthesized from pine cone petals by a chemical activation process and subsequently evaluated as an electrode material for supercapacitor applications in a nonaqueous medium. The maximum specific surface area of ∼3950 m2 g−1 is noted for the material treated with a 1:5 ratio of KOH to pine cone petals (PCC5), which is much higher than that reported for carbonaceous materials derived from various other biomass precursors. A symmetric supercapacitor is fabricated with PCC5 electrodes, and the results showed enhanced supercapacitive behavior with the highest energy density of ∼61 Wh kg−1. Furthermore, outstanding cycling ability is evidenced for such a configuration, and ∼90 % of the initial specific capacitance after 20 000 cycles under harsh conditions was observed. This result revealed that the pine-cone-derived high-surface-area AC can be used effectively as a promising electrode material to construct high-energy-density supercapacitors.